The Dynamics of Legal Protection For Notaries In Performing Notarial Duties - Rachel Gunawan; Benny Djaja; Maman Sudirman (Dinasti Research, 2025)
This study examines the problem of the dynamics of legal protection related to the weaknesses of the dual position regulation of Notaries in the Law on Notary Positions, which creates legal uncertainty and potential conflicts of interest. First, the inconsistency between Article 11 paragraph (1) which allows Notaries to take leave while serving as state officials with other articles that require total dismissal creates legal confusion. Differences in interpretation regarding